Coal Mine Gas Explosion Vulnerability Assessment Based on the "Glass Heart" Model. (24th April 2021) - Tian, Shuicheng; Yang, Pengfei; Tang, Kai
Abstract : Gas explosion, which is the main type of accidents reported in coal mines, comes with serious economic and safety consequences. The present work adopts the "glass heart" model for assessing the vulnerability of coal mines to gas explosions based on a constructed gas explosion vulnerability assessment index system. The proposed index system is applied to a coal mine in Henan Province, China, as an example. The original disturbance index is augmented by including the energy release index factor. The Delphi method is employed by six experts to score the index factors according to a scoring standard. Data analysis and processing yield a gas explosion vulnerability score of 0.431 for the example mine. Accordingly, the mine is classified as grade II, indicating that the mine is likely to result in casualties and/or property loss. A comparison of the assessment results with those obtained via an analysis of records pertaining to previous gas explosion accidents indicates that the proposed assessment of gas explosion vulnerability by means of the "glass heart" assessment model is realistic. The "glass heart" vulnerability assessment method offers a new perspective and methodology for assessing the vulnerability of coal mines to gas explosion and conducting coal mine risk classification.